Digital Readiness and Big Data Analytics: Moderating Roles in Achieving Social Sustainability through AI-CRM and Competitive Advantage - Dzingai Katsamba (Journal of Management Practices, Humanities and Social Sciences, 2025)
By empirically examining the impact of digital technology readiness on information technology capability and the adoption of artificial intelligence-based customer relationship management (AI-CRMA), and ultimately on competitive advantage and social sustainability performance, this study adds to the body of existing literature. We analyze the company's social sustainability performance using primary data from 344 samples. Based on the resource-based perspective paradigm, we discovered a positive correlation between digital technology readiness and the moderating effect of ICT on AI-CRM capabilities. Big data analytics capacity significantly influences the adoption of AI-CRM and digital technology-prepared analytics. Competitive advantage and social sustainability performance are significantly and favorably correlated. One of the study's main conclusions is that competitive advantage and digital technology preparedness are mediated by AI-CRM adoption. Furthermore, the relationship between AI-CRM adoption and social sustainability performance is mediated by competitive advantage.